EFFECT OF ENTREPRENEURIAL ENTHUSIASM ON ATTITUDE TOWARDS TRAFFIC SAFETY AMONG TRICYCLE RIDERS IN RIVER STATE - Oba Egwe , Cordelia (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2023)
Within entrepreneurship, motivation describes the psychological investment geared towards attaining a set business goal. Indeed, motivation is an essential component in the transportation business. Given the increasing disregard for traffic safety associated with the transportation business in Nigeria, research must explore the relevant variables that could correlate with the behavior of motorists toward traffic safety. Thus, the present study aims to examine entrepreneurial motivation as a factor that could account for the variation in attitudes toward traffic safety among tricycle drivers in the River State of Nigeria. One hundred and thirteen tricycle operators operating in different locations in the state were recruited for the study. The participants comprised males aged 20 to 45 years with about one year of driving experience. They completed a self-report measure of the Attitude towards Safe Driving Scale (ASDS) and the entrepreneurial motivation questionnaire. The simple regression analysis conducted on the data revealed that entrepreneurial motivation statistically significantly predicted attitudes toward traffic safety. Thus, the study concluded that entrepreneurial motivation is an essential determinant of drivers' attitudes toward traffic safety.